Mental illness of the oldest, nutritional status and arterial hypertension - Mayor, M. S.; Pestana, M. H.; Reis, M.Gorete; Santos, J. M. (International Journal of Statistics and Applications, 2015)
Changes in nutritional status and high blood pressure are very common in elderly with mental disorders. Currently, the interest in knowing associated factors to those variables is to prevent morbidity and mortality risk. The study aim was to evaluate the relationship between mental disorders, nutritional status and blood pressure. It´s a cross-sectional study in a sample of 99 elderly living in community that had a psychiatric emergency episode. Data were collected from the initial evaluation form (IE). Results show multiple pathologies, cognitive deficits, high blood pressure and change in body mass index (BMI). Conclusion: In most of the sample BMI is associated with several co morbidities and co-exists with a temporal disorientation and arterial hypertension. Prevention is the key to maintaining health and well-being.